2018
DOI: 10.1158/1078-0432.ccr-18-0426
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/IIa Trial Using CD19-Targeted Third-Generation CAR T Cells for Lymphoma and Leukemia

Abstract: The chimeric antigen receptor (CAR) T-cell therapy has been effective for patients with CD19 B-cell malignancies. Most studies have investigated the second-generation CARs with either CD28 or 4-1BB costimulatory domains in the CAR receptor. Here, we describe the first clinical phase I/IIa trial using third-generation CAR T cells targeting CD19 to evaluate safety and efficacy. Fifteen patients with B-cell lymphoma or leukemia were treated with CAR T cells. The patients with lymphoma received chemotherapy during… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(161 citation statements)
references
References 29 publications
2
149
2
Order By: Relevance
“…Moreover, it was shown that the degree of intracellular signaling activity of 3G CART cells was higher than of 2G CART cells and probably resulted in superior cell proliferation . First clinical studies with CD19‐specific 3G CART cells demonstrated efficiency and safety in patients with B cell malignancies . The aim of this study was to further improve the generation of these potentially superior 3G CART cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that the degree of intracellular signaling activity of 3G CART cells was higher than of 2G CART cells and probably resulted in superior cell proliferation . First clinical studies with CD19‐specific 3G CART cells demonstrated efficiency and safety in patients with B cell malignancies . The aim of this study was to further improve the generation of these potentially superior 3G CART cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I dose-escalation study, Ramos et al 56 active disease responded to treatment, including three complete responses (CRs). Enblad et al 58 reported the outcomes of 15 patients with r/r B-cell malignancies treated with autologous anti-CD19 CAR T cells incorporating both CD28 and 4-1BB costimulatory domains, four of whom did not receive lymphodepletion before CAR T cell infusion. 56,57 In 10 out of 11 patients with active disease, greater expansion (up to 40-fold) of third-generation CAR T cells compared to second-generation CAR T cells was seen, and third-generation CAR T cells remained detectable at higher levels up to 160 days postinfusion.…”
Section: Combining Costimulatory Domainsmentioning
confidence: 99%
“…One case of severe cytokine release syndrome (CRS) and one case of severe CAR T cell-related encephalopathy syndrome (CRES), also referred to as immune effector cell-associated neurotoxicity syndrome (ICANS), were observed. 36,58,59 Third-generation CAR T cells incorporating the Toll/interleukin-1 receptor (TIR) domain of Tolllike receptor 2 (TLR2), together with the CD3f and CD28 intracellular domains, were administered to three patients with an extramedullary relapse of B-ALL. Moreover, only third-generation CAR T cells expanded significantly when infused to patients in remission after autologous stem cell transplantation, suggesting the third-generation CAR T cells can expand despite minimal CD19 antigen exposure.…”
Section: Combining Costimulatory Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…These second‐generation CAR‐T therapies have been used in the seminal CAR‐T trials in CD19 and/or CD22 expressing malignancies . More recently, investigators have been researching methods to leverage current CAR‐T and increase persistence and/or cytolytic effect by incorporating various combinations of co‐stimulatory molecules including: 4‐IBB, CD27, CD134, and ICOS . The inclusion of suicide genes such as icasp9, surface marker depletions of EGFR and other analogous mechanisms to destroy CAR‐T at a clinically indicated time are also being investigated …”
Section: Efficacy Of Car‐t In Hematologic Malignanciesmentioning
confidence: 99%